Politics and post-structuralism : an introduction - Finlayson, Alan; Valentine, Jeremy (Edinburgh University Press, 2002)
Post-structuralism is recognised as a major force within literary and cultural studies. This text applies the theory to politics and to show the ways in which it can illuminate political theory and analysis.
Keywords: Poststructuralism.; Political science -- Philosophy.; Idées politiques.; Poststructuralisme.; post-structuralism.; PHILOSOPHY -- Political.; Political science -- Philosophy; Poststructuralism